2013
DOI: 10.2478/bvip-2013-0089
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of extended spectrum β-lactamaseand AmpC-producing Escherichia coli in meat samples

Abstract: The aim of the study was a preliminary determination of occurrence of extended spectrum β-lactamases (ESBL)-and AmpC-producing Escherichia coli (E.coli) in raw meat samples collected from slaughter-houses located in different regions of Poland. A total of 141 samples were tested, comprising 78 pork samples, 44 beef samples, and 19 chicken meat samples. Isolated and identified E. coli strains were examined for the ESBL and/or AmpC β-lactamases production by the use of four disc diffusion and minimum inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Wasiński et al [38] have revealed the number of cephalosporin resistance occurring on farms. The incidence of resistance to cephalosporins has been widely reported and has a lot to do with pig farming [39].…”
Section: Resultsmentioning
confidence: 99%
“…Wasiński et al [38] have revealed the number of cephalosporin resistance occurring on farms. The incidence of resistance to cephalosporins has been widely reported and has a lot to do with pig farming [39].…”
Section: Resultsmentioning
confidence: 99%
“…This result is lower than 9.4% isolation prevalence of ESBLs-producing E. coli reported by Chah and Oboegbulem (2007) among 171 ampicillinresistant E. coli isolates from chicken in Nigeria. Smet et al (2008), Geser et al (2011), Garcia-Graells et al (2010 and Wasinski et al (2013) reported 60, 92.3, 42 and 11.7% isolation prevalence of ESBLs-producing E. coli in poultry carcasses in Belgium, broilers in Belgium, pigs and cattle in Switzerland, and meat samples in Poland, respectively. In the Netherlands, Overdevest et al (2011) and Leversteinvan Hall et al (2011) reported 80 and 94% prevalence of ESBLs-producing E. coli in chicken meat and raw meat, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The group of 18 ESBLproducing and 7 AmpC-producing E. coli isolated from 141 meat samples, including 78 samples of pork, 44 samples of beef, and 19 samples of poultry (Gallus gallus), was investigated. The production of β-lactamases was determined earlier by the use of disk test D68C (Mast Diagnostica, Germany), confirmatory MIC test Sensititer ® ESBL (Trek Diagnostic System, UK), and by polymerase chain reaction (PCR) as previously described (20). (12).…”
Section: Methodsmentioning
confidence: 99%